2017
DOI: 10.1177/0379572117726422
|View full text |Cite
|
Sign up to set email alerts
|

Making Food Aid Fit-for-Purpose in the 21st Century: A Review of Recent Initiatives Improving the Nutritional Quality of Foods Used in Emergency and Development Programming

Abstract: Important strides have been made recently in upgrading the global food aid agenda in line with evolving medical and nutrition sciences, operational experience, and innovations in food technology. A 2011 report endorsed by the United States Agency for International Development (USAID) recommended numerous improvements to products intended to support improved survival and nutrition in humanitarian programming, as well as greater rigor and transparency in the research agenda that supports innovations in this crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Portner (2010) pointed out that each disaster occurrence increased the prevalence of stunting among children. The bulk of food aid takes the form of grains, which mainly contain carbohydrates (Webb et al 2017;Dhoubhadel et al 2020). A study conducted after the 2011 Great East Japan Earthquake (GEJE) by Inoue et al (2014) showed that most food aid received, such as rice balls or bread, was carbohydrate-based, possibly because of their ready provision and abundance in emergency food pantries.…”
Section: Macro-nutrient and Micro-nutrient Deficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Portner (2010) pointed out that each disaster occurrence increased the prevalence of stunting among children. The bulk of food aid takes the form of grains, which mainly contain carbohydrates (Webb et al 2017;Dhoubhadel et al 2020). A study conducted after the 2011 Great East Japan Earthquake (GEJE) by Inoue et al (2014) showed that most food aid received, such as rice balls or bread, was carbohydrate-based, possibly because of their ready provision and abundance in emergency food pantries.…”
Section: Macro-nutrient and Micro-nutrient Deficienciesmentioning
confidence: 99%
“…Emergency interventions to protect poor people should not simply be for gross caloric intake, but the quality of children's diets as well (Block et al 2004). This quantity and quality can be achieved by ensuring access to safe and nutritious foods, particularly for children to reduce levels of wasting and micronutrient deficiencies (Webb et al 2017). Food rations must be fortified with essential micronutrients (Toole 1992;Pradhan et al 2016).…”
Section: Macro-nutrient and Micro-nutrient Deficienciesmentioning
confidence: 99%
“…"Food assistance has become a key element of humanitarian aid to conflict-affected populations, intended to promote the survival and growth of infants and young children" [5,6]. Throughout human history, humanitarian food aid was provided in the form of food or non-food items for people affected by famine, drought, or natural disaster [4,[7][8][9]. Hunger and undernutrition can significantly worsen during situations of prolonged conflicts and where institutional capacities are weak [3].…”
Section: Introductionmentioning
confidence: 99%
“…Food aid provided in the form of general food parcels distribution (FPD), such as food banks, food pantries or emergency food boxes, can be the only source of nutrition, or a crucial diet complementation for food insecure communities and vulnerable individuals worldwide during crisis (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%